2004
DOI: 10.1074/jbc.m313329200
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) Polymerase-1-mediated Cell Death in Astrocytes Requires NAD+ Depletion and Mitochondrial Permeability Transition

Abstract: Extensive activation of poly(ADP-ribose) polymerase-1 (PARP-1) by DNA damage is a major cause of caspase-independent cell death in ischemia and inflammation. Here we show that NAD ؉ depletion and mitochondrial permeability transition (MPT) are sequential and necessary steps in PARP-1-mediated cell death. Cultured mouse astrocytes were treated with the cytotoxic concentrations of N-methyl-N-nitro-N-nitrosoguanidine or 3-morpholinosydnonimine to induce DNA damage and PARP-1 activation. The resulting cell death w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
336
2
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 350 publications
(355 citation statements)
references
References 60 publications
12
336
2
5
Order By: Relevance
“…Interestingly, repletion of NAD + after PARP-1 activation has been shown to restore glycolytic capacity and prevent cell death (Ying et al, 2003(Ying et al, , 2005 in primary neuronal cultures. Similarly, providing nonglucose substrates such as pyruvate and a-ketoglutarate that can be metabolized without the need for cytosolic NAD + also preserves cell viability, even when delivered hours after PARP-1 activation (Alano et al, 2004;Ying et al, 2002). However, to be used oxidatively, lactate must be first converted to pyruvate by lactate dehydrogenase, which also requires NAD + and thus competes with glycolysis for NAD + .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, repletion of NAD + after PARP-1 activation has been shown to restore glycolytic capacity and prevent cell death (Ying et al, 2003(Ying et al, , 2005 in primary neuronal cultures. Similarly, providing nonglucose substrates such as pyruvate and a-ketoglutarate that can be metabolized without the need for cytosolic NAD + also preserves cell viability, even when delivered hours after PARP-1 activation (Alano et al, 2004;Ying et al, 2002). However, to be used oxidatively, lactate must be first converted to pyruvate by lactate dehydrogenase, which also requires NAD + and thus competes with glycolysis for NAD + .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in PARP-1 knockout mice and PARP-1-null neuronal cultures indicate that PARP-1 activation may signal this translocation step secondary to the poly(ADP-ribosyl)ation of unidentified nuclear proteins that translocate from the nucleus to the mitochondria (Hong et al, 2004;Yu et al, 2003). Studies in cultured astrocytes and other cells indicate that it is also possible that depletion of ATP and/or NAD þ in mitochondria, secondary to PARP-1 activation, signals mitochondrial AIF release (Alano et al, 2004). In any event, it is now well established that pharmacologic or genetic interruption of PARP-1 activation is cytoprotective in a wide variety of in vivo and in vitro models in response to an equally wide variety of injurious stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that ROS-mediated DNA damage triggers activation of the PARP-1 and subsequent cell death (30,31). Although PARP-1 -mediated cell death is thought to be necrotic (32,33), recent reports have shown that PARP-1 -mediated cell death also has many features in common with the apoptotic forms of cell death (30,31,34,35).…”
Section: Introductionmentioning
confidence: 99%